The Influence of Digital Tax and Taxpayer Awareness on Individual Taxpayer Compliance with Tax Socialization as a Moderating Variable (Study at the Lamongan Pratama Tax Service Office) - Rina Sulistyowati; Argik Fitro Magfiroh; Rita Nataliawati; Qosim (Program Studi Akuntansi Universitas Islam Lamongan, 2024)
This study seeks to evaluate the impact of digital taxation and taxpayer knowledge on individual compliance with tax socialization as a variable. This study employs quantitative methodologies. The study population included individual taxpayers registered with KPP Pratama Lamongan, using a basic random selection approach with a sample size of 100. The variables examined in this research are Digital Tax, Taxpayer Awareness which is the independent variable, Individual Taxpayer Compliance as the dependent variable and Tax Socialization as the moderating variable. The study data was examined using Moderated Regression Analysis (MRA) with the SPSS software. 26. The research results show that 1) Digital Tax does not have a positive and meaningful influence on individual taxpayer compliance, 2) Taxpayer knowledge positively and significantly influences individual taxpayer compliance, 3) Socialization of tax does not influence the impact of digital taxation on individual taxpayer compliance. individual, 4) Tax socialization moderates the impact of taxpayer knowledge on individual compliance.